Unraveling marketing strategies of prefabricated steel structure industry: analysis of McDonald Steel Building Products Limited - Ahmed, Rafat Tanvir (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2024.